The Inevitability of Teleology: From le Dispositif to Apparatus Theory to Dispositifs Plural - Gaines, Jane (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2011)
The article asks how problems of historical method are implied in the question “What Is Left of Apparatus Theory [...] ?”, the topic of the round table for which this paper was first delivered at the IMPACT conference. It goes on to recap the problems with traditional historical approaches : the “from…to” overview, the linear narrative, and the teleological expectation, to name a few. Then, it suggests, following Reinhard Koselleck, that teleologies (like the teleology to end all teleologies – the death of cinema) are unavoidable if one is functioning as a historian-positioned-in-time. Finally, it asks how we are to lay out Baudry and Foucault and trace the “adventures” of the apparatus and apparatus theory when the discourse theory that underwrote their projects critiques the project of “discovering” past events since in the end we are constituting the technology we discover, the same technology that we have said constitutes us.